Etiology and Outcomes of ARDS in a Rural-Urban Fringe Hospital of South India - Tarun George; Stalin Viswanathan; Ali Hasan Faiz Karnam; Georgi Abraham (Critical Care Research and Practice)
Objectives. Etiology and outcomes of acute lung injury in tropical countries may be different from those of western nations. We describe the etiology and outcomes of illnesses causing acute lung injury in a rural populace. Study Design. A prospective observational study. Setting. Medical ICU of a teaching hospital in a rural-urban fringe location. Patients. Patients ≥13 years, admitted between December 2011 and May 2013, satisfying AECC criteria for ALI/ARDS. Results. Study had 61 patients; 46 had acute lung injury at admission. Scrub typhus was the commonest cause (7/61) and tropical infections contributed to 26% of total cases. Increasing ARDS severity was associated with older age, higher FiO2 and APACHE/SOFA scores, and longer duration of ventilation. Nonsurvivors were generally older, had shorter duration of illness, a nontropical infection, and higher total WBC counts, required longer duration of ventilation, and had other organ dysfunction and higher mean APACHE scores. The mortality rate of ARDS was 36.6% (22/61) in our study. Conclusion. Tropical infections form a major etiological component of acute lung injury in a developing country like India. Etiology and outcomes of ARDS may vary depending upon the geographic location and seasonal illnesses.